Home Sweet Home: Skin Stem Cell Niches - Goldstein, Jill (2012)
The epidermis and its appendages, such as the hair follicle (HF), continually regenerate throughout postnatal mammalian life due to the activity of resident epithelial stem cells (SCs). The follicular SC niche, or the bulge, is composed of a heterogeneous population of self-renewing multipotent cells. Multiple intrinsic molecular mechanisms promote the transition of follicular SCs from quiescence to activation. In addition, numerous extrinsic cell types influence the activity and characteristics of bulge cells. Ultimately, the balance between these intrinsic and extrinsic mechanisms influences the function of bulge cells during homeostasis and tissue regeneration and likely contributes to skin tumorigenesis. Here we review both the intrinsic and extrinsic factors that contribute to the skin SC niche.